(untitled) (Bangladesh Journal of Medical Science, 2026)
Introduction After suffering a stroke, patients may experience limb paralysis, leading to a negative impact on their life and requiring longterm care both in the hospital and at home by the family. This integrative review identified scientific literature regarding family knowledge, roles, and support in caring patients with stroke. Methods This study was conducted as an integrative review. Article searches were conducted using ProQuest, Scopus, PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Ebsco, and Garuda for publications from 2015 to 2024, with full text available in English or in Indonesian. This review was referred on the Whittemore and Knafl framework, and for quality control, we utilized the Clinical Appraisal Prospective Study (CAPS) instrument. Results Nine qualitative articles were thoroughly checked and carefully extracted to reach a conclusion regarding family experiences in caring for patients with stroke, emphasizing knowledge, support, and family roles. The need for tailored educational and support programs for families caring for patients with stroke emphasizes the importance of enhancing family knowledge and skills, involving them in care decisions, and providing comprehensive support from healthcare professionals. Conclusions The role of the family is crucial in caring for family members with stroke at home. However, this review high light several limitations and challenges in caring for patients with stroke, including a lack of knowledge, skills, and significant economic psychosocial burden. Therefore, families need different types of information support and interventions from health providers in order to carry out their responsibilities optimally. BJMS, Vol. 25 No. 01 January’26 Page : 52-61